What we do not know about cerebellar systems neuroscience - Voogd, Jan (Frontiers in Systems Neuroscience, 2014)
Our knowledge of the the modular organization of the cerebellum and the sphere of influence of these modules still presents large gaps. Here I will review these gaps against our present anatomical and physiological knowledge of these systems.